‘Io ho abbastanza spirito per il Sud’: Nietzsche tra Napoli e Sorrento - Bocchetti, Andrea (Scenari, 2025)
This article aims to illustrate, through the story of the events surrounding Nietzsche’s first trip to Italy, the key moments that marked the German philosopher’s distancing from his ‘master’ Wagner. Between the summer and early autumn of 1876, the two met first in Bayreuth, then in Sorrento: this brief period was enough for a long and deep friendship to come to an end, due to the divergent spiritual paths the two took from that moment on.